Barron's SAT - Green, Sharon, 1939-; Wolf, Ira K. (New York : Barron's, 2010)
A guide to the SAT that features a test overview, study and test-taking strategies, full-length practice tests, a diagnostic test, vocabulary flash cards, subject reviews in critical reading, grammar, and mathematics, and other helpful resources.
Young Adult.
Young Adult
Keywords: SAT (Educational test) -- Study guides; Universities and colleges -- Entrance examinations; Colleges and universities -- Entrance examinations; SAT (Educational test) -- Study guides